Single channel properties of P2X ATP receptors in outside-out patches from rat hippocampal granule cells - Wong, Adrian YC (Blackwell Science Inc, 2000)
1. The single channel properties of P2X ATP receptors were investigated in outside-out patches from hippocampal granule cells in brain slices from 12-day-old rats. The results demonstrate that functional P2X ATP receptors are expressed in hippocampal granule cells and, combined with previously published information on the P2X subunits expressed in the hippocampus, suggest that the receptors may be heteromers of the P2X(4) and P2X(6) subunits or P2X(1), P2X(2), P2X(4) and P2X(6) subunits. 2. Two distinct types of P2X channel openings were observed. A flickery P2X receptor channel was observed in three patches with a mean chord conductance of 32 ± 6 pS, a mean open time of 1.0 ± 0.3 ms and a mean burst length of 11 ± 5 ms at a membrane potential of −60 mV. A large conductance P2X receptor was observed in 19 out of 98 patches with a mean conductance of 56 ± 1.8 pS, a linear current-voltage relationship between −80 and +60 mV with a reversal potential around 0 mV, a mean open time of 2.6 ± 0.2 ms and a mean burst length of 8.8 ± 1.8 ms at −60 mV. At an ATP concentration of 1 mm, these channels exhibited a low steady-state open probability (P(open), 0.07 ± 0.008; n = 15), little apparent desensitisation and were also activated by α,β-methylene ATP (α,β-meATP, 40 μm; P(open), 0.007 ± 0.0002; conductance, 57 ± 1.1 pS; n = 3). No decrease in the single channel conductance was observed on increasing the free extracellular calcium concentration from 0.3 to 0.85 mm. 3. Channel closed time distributions were fitted with five exponential components with time constants (and relative areas) of 90 μs (20%), 0.77 ms (32%), 10 ms (15%), 90 ms (18%) and 403 ms (15%) at 1 mm ATP. Of these, the first two components are suggested to represent gaps within single activations of the receptor based on the lack of agonist concentration dependence of these two shut time components between 1 μm and 1 mm ATP. 4. Suramin (40 μm) significantly increased the single channel conductance (19 ± 7%; n = 5) and produced a small decrease in P(open) (39 ± 9%; n = 5) by decreasing mean open time, burst length and total open time per burst. These actions of suramin are not consistent with simple competitive antagonism.